2022
DOI: 10.1177/00207640221094155
|View full text |Cite
|
Sign up to set email alerts
|

Fixating on the future: An overview of increased astrology use

Abstract: Background: Interest in astrology has surged recently, possibly due to the uncertain conditions in the world due to the Covid-19 pandemic. While belief in astrology is common and socially legitimized in many cultures, a few instances of excessive engagement with astrological services or “fortune-telling addiction” are indicating a risk of adverse mental health consequences. Aim: To understand the existing research base on correlates of belief in astrology and fortune-telling. Method: We have carried out a scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Nevertheless, some evidence supports this potential link. Firstly, data showed that adolescents sought support from some personality assessments when encountering psychological problems ( Archer et al, 1991 ; Rickwood et al, 2007 ; Das et al, 2022 ). This indicates positive implications of personality assessments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some evidence supports this potential link. Firstly, data showed that adolescents sought support from some personality assessments when encountering psychological problems ( Archer et al, 1991 ; Rickwood et al, 2007 ; Das et al, 2022 ). This indicates positive implications of personality assessments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When encountering psychological problems, adolescents prefer seeking self-help information support ( Rickwood et al, 2007 ). Among them, personality assessments are favored, including some low-scientific ones ( Archer et al, 1991 ; Das et al, 2022 ). However, whether and how personality assessments affect adolescent mental health remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ancient Greek cultures, fortune tellers, and magazines in horoscope readings proposed that constellations and planetary alignments have predictive properties specified toward zodiac signs. Amid the COVID-19 pandemic, there has been an upsurge in the utilization of the Chinese and Western Zodiac, likely related to the uncertain conditions worldwide [9]. In a recent evaluation of vaccination rates, the Salt Lake City Health Department identified different vaccination rates based on Zodiac signs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Эзотерические и паранормальные практики представляют сегодня значительный сектор услуг, на который есть спрос в России [4] и мире [15]. При этом предикторы обращения к ним до сих пор слабо изучены [1].…”
Section: Introductionunclassified